2019
DOI: 10.1007/s13762-019-02316-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different iron oxide adsorbents for combined arsenic, vanadium and fluoride removal from drinking water

Abstract: Contamination of groundwater by arsenic due to natural processes is rather common worldwide and hinders its use for drinking water supply. In many cases, arsenic contamination is found together with high levels of vanadium and fluoride. Therefore, more than one type of treatment is required to reduce concentrations of all these contaminants below non-hazardous levels so to make the source drinkable. The present study investigated the uptake capacity of arsenic, vanadium and fluoride by three iron-based adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…31/2001). Among the 6 adsorbents used with the synthetic solution, this series of tests was conducted using only TiO 2 , A33E and GFH, since they are reported to possess a high removal capability versus arsenic in liquid solutions [21,25,[27][28][29][30][31]. Under real conditions of application, there would be the need to reduce both fluoride and arsenic concentrations below the respective limits.…”
Section: Adsorption Kinetic Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…31/2001). Among the 6 adsorbents used with the synthetic solution, this series of tests was conducted using only TiO 2 , A33E and GFH, since they are reported to possess a high removal capability versus arsenic in liquid solutions [21,25,[27][28][29][30][31]. Under real conditions of application, there would be the need to reduce both fluoride and arsenic concentrations below the respective limits.…”
Section: Adsorption Kinetic Experimentsmentioning
confidence: 99%
“…Then, the mass of contaminant transferred by adsorption per unit weight of adsorbent at equilibrium (i.e., the adsorption capacity), Q e , was calculated by applying Equation (1). The results from the isotherm experiments were fitted by the Freundlich, Langmuir, Brunauer-Emmett-Teller (BET) and Temkin models [21] (Table 5). The best-fitting model was considered as one providing the higher value of the correlation coefficient (R 2 ) between the experimental and model-predicted data using the linearized form of the representative equation.…”
Section: Adsorption Isotherm Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron oxide is a compound material, largely found as hematite (α-Fe 2 O 3 ), magnetite (Fe 3 O 4 ), wüstite (Fe 1– x O), and maghemite (γ-Fe 2 O 3 ), which has attracted attention as an adsorbent due to its ability to remove various types of heavy-metal ions. Recent studies have demonstrated that α-Fe 2 O 3 has a high adsorption capability, which occurs through a chemisorption process involving the hydroxyl group on its surface . Ren et al investigated α-Fe 2 O 3 in a fibrous form for Cr­(VI) ion removal and reported that the porous fiber-like morphology of α-Fe 2 O 3 exhibited excellent adsorption of Cr­(VI) from water, with rapid adsorption kinetics, high adsorption capacity, and good reusability .…”
Section: Introductionmentioning
confidence: 99%